2018
DOI: 10.1186/s40246-018-0181-3
|View full text |Cite
|
Sign up to set email alerts
|

Link between short tandem repeats and translation initiation site selection

Abstract: BackgroundDespite their vast biological implication, the relevance of short tandem repeats (STRs)/microsatellites to the protein-coding gene translation initiation sites (TISs) remains largely unknown.MethodsWe performed an Ensembl-based comparative genomics study of all annotated orthologous TIS-flanking sequences in human and 46 other species across vertebrates, on the genomic DNA and cDNA platforms (755,956 TISs), aimed at identifying human-specific STRs in this interval. The collected data were used to exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Repeat elements have long been thought to have functional, mutational and evolutionary significance [25, 26] and experimental evidence of a role for SSRs is increasingly available, albeit in only a few species per study (reviewed in [27]). While this manuscript was being reviewed, another study was published that showed differential distribution of human-specific SSRs at translation initiation sites [28] with implications for directing species-specific translation events and thus the phenotype. Such studies bolster recent work on the evolutionary trends and influence of SSRs in defining species specificity and warrant larger scale analysis across the evolutionary landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat elements have long been thought to have functional, mutational and evolutionary significance [25, 26] and experimental evidence of a role for SSRs is increasingly available, albeit in only a few species per study (reviewed in [27]). While this manuscript was being reviewed, another study was published that showed differential distribution of human-specific SSRs at translation initiation sites [28] with implications for directing species-specific translation events and thus the phenotype. Such studies bolster recent work on the evolutionary trends and influence of SSRs in defining species specificity and warrant larger scale analysis across the evolutionary landscape.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The STR polymorphisms might lead to alternative splicing of the DMT1 gene. A recent study has proposed that there is a link between short tandem repeats and translation initiation site selection in humans [31]. Previous studies have reported the existence of isoforms of DMT1 mRNA [32, 33] and protein [33], suggesting alternative splicing of the DMT1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a TIS homology approach, we recently reported a link between STRs and TIS selection (31). Here, we extended our weighing methods, and developed a comprehensive software package, to study a possible link between all categories of TRs and TIS selection across 84 species.…”
Section: Introductionmentioning
confidence: 99%